Morphological variability and management of Lonand sheep of Maharashtra - Yadav , Dinesh Kumar; Arora, Reena; Jain, Anand (Journal of Livestock Biodiversity, 2025)
To characterize Lonand sheep of Maharashtra, 7 morphometric traits (height at withers, body length, chest girth, paunch girth, ear length, tail length and body weight were recorded on 114 animals. The study included animals having 2-8 tooth. Management practices, production and reproduction traits were recorded using interview method. The average body weights of rams and ewes were 42±3.69 and 29.3±0.45 kg whilst the chest girths were 81.3±2.25 and 74.4±0.37 cm respectively. Males were 47% heavier than females. The coefficient of variation of all traits ranged from 3.8 % to 27.8 %. The average lock size of 41 locks was 85.7 which comprised 65.2 ewes, 1.6 rams and 18.9 lambs. The animals were primarily maintained under extensive management system. The locks were migratory, mostly within the Satara district. Introduction of Madgyal rams in locks was observed. Breed purity was 14.7 %. Age at irst lambing was 16-18 months. Daily milk yield was 200 ml and lactation length was 90 days. Average annual greasy wool yield was around 500 gm. The study has contributed to the knowledge of morphometric characterization and population structure of Lonand sheep, and would enable to have insight for its conservation and improvement programmes.